PRESEVATION OF COTTON FISH NET TWINES BY TANNING : I. OPTIMUM CONCENTRATION OF TANNING BATH - CECILY, (Smt.) P. J; KUNJAPPAN, M K. (Fishery Technology, 2025)
Samples of tannin-containing preservatives used by fishermenlin India for treating cotton nets were collected and qualitativeand quantitative characterisation of the tannins made. The concentrationsof different tannins required to impart optimum periodsof preservation to the net were worked out and found to be 2%in 8 out of 10 materiaJs studied.